BS EN ISO 19403-5. Paints and varnishes. Wettability. Part 5. Determination of the polar and dispersive fractions of the surface tension of liquids from contact angles measurements on a solid with only a disperse contribution to its surface energy (22nd September 2023) - British Standards Institution
No abstract available